PERENCANAAN JARINGAN AIR BERSIH DESA DIENG KEJAJAR WONOSOBO - Ashal Abdussalam; Akhmad Lutfatul Latif (Jurnal Teknik Sipil, 2018)
Water is a basic need for human life, because water is a very important macro nutrient. Clean water is water that is used for daily needs whose quality meets health requirements and becomes drinking water after being cooked first. Dieng Village, Kejajar Subdistrict, Wonosobo  Regency  is  a  village  that  has  a  contour  of  hilly  land  and  also  has  abundant springs. From the information of the local residents, the condition of the well water that they use everyday is possible to have contaminated sulfur based on the aroma felt by the community.  So  that  clean  water  planning  is  needed  for  the  community  to  replace unhealthy well water. The data used as a basis for making journals are grouped into two types, namely primary data and secondary data. From observations and observations it is known that the spring discharge is 1.5 l / second. This figure is enough to meet the water needs of the population for the next 15 years which is approximately 2.73 l / sec with a total  user  of  1,488  people.  Supporting  buildings  are  planned  by  calculation  and  pay attention to the situation in the actual location. From this, broncaptering buildings were obtained with dimensions of 2m  x 2m x 1.5m and  building buildings with dimensions of 4m x 4m x 3m. The total cost needed to implement this plan is Rp. 915,195,894.16.- at a price of Rp. 4,100.00.- per m3.